The foot patrol - Sevastian, Dragos-Robert (Eximia, 2023)
Patrolling is the organized police tactical activity, through which the presence of police officers is achieved in the field, in a certain period of time on a well-established itinerary, in relation to the requirements of the operational situation in the territory of competence. The pedestrian patrol acts to ensure visibility and prevention, in patrolling areas with a complex operational situation where a large number of people, commercial units, public institutions, etc. are concentrated. and where access by car is difficult or impossible. The policeman must respond to any legitimate request of the citizens and not harm the image of the institution he represents through behavior and attitudes inconsistent with his professional status. The activities of the policemen from the patrols: - acts permanently to prevent and combat anti-social acts and other manifestations that violate the norms of social coexistence, public order, traffic on public roads and harm the rights and freedoms of citizens, the life and bodily integrity of the person, public and private property, taking firm measures, according to the legal provisions, when these facts have been committed; - intervene to ensure the flow of traffic in the patrol areas, when the situation requires it; - ensures the maintenance of public order during the occurrence of natural calamities, catastrophes, disasters, as well as for limiting their effects by taking the first measures; - they intervene in the events signaled by 112, on the principle that the most appropriate police officer at the place of the event intervenes, regardless of their nature and territorial competence; - draw up the preliminary documents, in the case of flagrant detection of a criminal act; - take the suspicious persons to the police headquarters in order to take the necessary legal measures; - intervene promptly to resolve certain situations, found ex officio or at the request of citizens;